ADY1, A Novel Gene Required for Prospore Membrane Formation at Selected Spindle Poles in Saccharomyces cerevisiae - Deng, Changchun (The American Society for Cell Biology, 2001)
ADY1 is identified in a genetic screen for genes on chromosome VIII of Saccharomyces cerevisiae that are required for sporulation. ADY1 is not required for meiotic recombination or meiotic chromosome segregation, but it is required for the formation of four spores inside an ascus. In the absence of ADY1, prospore formation is restricted to mainly one or two spindle poles per cell. Moreover, the two spores in the dyads of the ady1 mutant are predominantly nonsisters, suggesting that the proficiency to form prospores is not randomly distributed to the four spindle poles in the ady1 mutant. Interestingly, the meiosis-specific spindle pole body component Mpc54p, which is known to be required for prospore membrane formation, is localized predominantly to only one or two spindle poles per cell in the ady1 mutant. A partially functional Myc-Pfs1p is localized to the nucleus of mononucleate meiotic cells but not to the spindle pole body or prospore membrane. These results suggest that Pfs1p is specifically required for prospore formation at selected spindle poles, most likely by ensuring the functionality of all four spindle pole bodies of a cell during meiosis II.